Implementasi Sistem IoT Berbasis Deteksi Bunyi Menggunakan Sensor Suara untuk Otomatisasi Pencahayaan Rumah - M. Rifqi Yudi Prayoga (Computer Journal, 2026)
Recent developments in the technology of the Internet of Things (IoT) have led to a more convenient and contactless home automation system. This paper presents an IoT-based home lighting automation system using KY-038 sound detection as a trigger. The functioning principle is based on sound intensity exceeding a certain threshold, which is then processed by an ESP32 microcontroller to control lighting via Wi-Fi in real-time without the need for physical switches. This does not relate to any voice recognition system that uses cloud-based processing, but rather provides simplicity and faster response time through local processing. Testing was done on the performance of the system with variations in distance and sound intensity, where each scenario was repeated 10 times for validation purposes Experimental results show that detection accuracy of 90-100% up to 3 meters with response times between 0.8-1.1 seconds. The system has been tested indoors under conditions of low to moderate ambient noise levels and found reliable operation. It can be integrated with IoT platforms for remote monitoring as well as manual control from mobile applications. This implementation will be very convenient for users especially those having limited mobility and can support energy efficiency in smart home environments by activating lights only when necessary.